KAJIAN EFISIENSI PADA KELOMPOK TIANG DENGANKONFIGURASI 2 X 2 - Herwin, -; Priadi, Eka; Aprianto, - (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2017)
The most important part that must be known in the construction planning of a construction is the condition of the land where the construction is built. In the Kalimantan area, especially in Pontianak city, it is generally a soft soil with a surface layer containing organic compound resulting from natural vegetation and good soil bearing capacity can be found at depths ranging from 30 to 40 meters. To overcome the poor soil conditions, the initial work was done to improve the carrying capacity of the soil. One of the most common ways is the use of piles. The possibility of construction standing on single pile is very rarely used, at least used two or more piles. The number in the pile group has different efficiency values because the number of poles influences the efficiency of the pole group. Thus, in this test, preparation of pile group load testing will be done with the same configuration and number of poles with different pole spacing 3 times the pole diameter (3D) and 4 times the pole diameter (4D). This is done to find out how much influence the distance between poles on the efficiency of the pole group. And from the test results, the efficiency obtained in the 3D distance pole group has a smaller efficiency than the pole group at a distance of 4D. This is because the spreading factor around the pole Overlapping will be smaller if the distance between the poles is greater.Â